Pengaruh Ketersediaan Barang dan Persepsi Harga Terhadap Keputusan Pembelian Ponsel - Husna, Asmaul; Syafitri, Fadila; Sarwoto, Sarwoto; Candrassa, Limega (Forum Kerjasama Pendidikan Tinggi, 2025)
The purpose of this study was to determine whether the availability of goods and price perceptions affect purchasing decisions at the Habib Ponsel Store. SPSS version 25 software was used in this study. Non-probability sampling combined with accidental sampling was the sampling technique used. Using the Taro Yamane formula to collect data. The respondents in question were customers at the Habib Ponsel store. Instrument Test Analysis (Validity Test and Reliability Test), Classical Assumptions, Normality, Multicollinearity, Heteroscedasticity, Multiple Linear Regression Analysis, Coefficient of Determination, t-test and f-test were all used in the data analysis methodology of this study. The findings of this study are as follows: 1. Availability of Goods is a consideration in making a purchase. 2. Price perception is considered appropriate for making a purchase. 3. Availability of goods and price perception are considerations when making a purchase. The test results that have been carried out show that the t-value for the variable of goods availability (X1) is 7.201, t-table 1.987, thus t-count is greater than t-table, significant value 0.000 <0.05, then Ho is rejected and H1 is accepted, meaning that the availability of goods (X1) has a positive and significant effect on purchasing decisions (Y). The price perception variable (X2) shows a t-value of 5.142, t-table 1.987, thus t-count is greater than t-table, significant value 0.000 <0.05, then Ho is rejected and H2 is accepted, meaning that price perception (X2) has a positive and significant effect on purchasing decisions (Y). The variables of goods availability (X1) and price perception (X2) obtained significant results on purchasing decisions, the results of this study showed a calculated F value of 108.722, Ftable 3.10 thus Fcount is greater than Ftable, the significant value is 0.000 <0.05 then Ho is rejected and H3 is accepted meaning that the availability of goods (X1) and price perception (X2) simultaneously have a significant effect on purchasing decisions (Y).